Modeling the contact dispensing process of conductive adhesives with different viscosities and optimization of droplet deposition - Zou, Jiajia; Huang, Mengqiu; Zhao, Dan; Chen, Fang; Wang, Daochang (Frontiers in Materials, 2023)
The contact dispensing process is composed of extrusion, stretching, and liquid bridge breakage, which is greatly impacted by the viscosity and surface tension of the dispensed liquid and the contact angle between the liquid and the substrate. Regarding contact dispensing of conductive adhesives, few studies have investigated the influence of the viscosity of conductive adhesives on the dispensing process. In the present study, computer simulation was used to explore the contact dispensing process of high-viscosity adhesives, and a dispensing device was designed to verify the simulation results. The results showed that the viscosity of the adhesives had the greatest influence on the dispensing process, and the higher the viscosity, the more difficult it was to break the liquid bridge, which seriously affected the stability of the contact dispensing process. In the dispensing process, once the adhesive had filled the gap between the needle tip and the substrate, increasing the dispensing time caused the diameter of the droplet to increase. Decreasing the lifting speed of the needle allowed sufficient time for the adhesive surface to restore changes caused by stretching, thereby eliminating unstable droplets and achieving droplets with regular morphology. In conclusion, our results demonstrated that computer simulation is a powerful tool for providing key information to improve the contact dispensing process, obtain droplets with optimal morphology, and achieve excellent bonding between the conductive adhesive and the substrate.